Excavating humanness: palaeoanthropology at the human-animal boundary - Goulden, Murray S. (2009)
The human-nonhuman animal boundary marks the interchange between human and animal, culture and nature, the social and the natural. This powerfully symbolic site has traditionally been structured via religion-based ideas of humanity's origins, that in the West have been used to maintain a strictly impermeable boundary: humans, created in God's own image and blessed with a soul on one side, on the other the senseless, soulless beast. This image is one which has come under threat from work in multiples branches of the natural and social sciences; in the humanities; and from animal rights activists and other social movements. Such culturally contested territory makes fertile ground for the study of interactions between science and popular culture, framed via Gieryn’s concept of 'boundary-work' (1983), and Bowker & Star’s sociology of classification (2000).